The worldview of malay muslim youths in the virtual world of second life : a case study - Norhayati Mohd Yusof (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This is a qualitative study on the worldview of Malay Muslim youths in the virtual world of second life represented by a group called SL1Malaysia. The main objective of this research is to investigate the elements of the worldview of the Malay Muslim youths through the representation of their senses, thoughts and actions via their virtual avatars and the extent to which their worldview in Second Life is compatible or dissonant with the Islamic worldview. This research is an extension of a previous exploratory study designed to identify the impact of participation in Second Life on religious understanding and practices among Muslim users. The informants for this research consist of a group of 6 active, closely-knit, loyal members of SL1Malaysia inhabiting the Second Life virtual environment. This study employs Kozinet's model of netnography, a qualitative method specially formulated for the study of virtual communities designed for online fieldwork. The findings of this study depicted elements of escapism, behaviour modelling, religious activity and sexual role-playing, and informants' virtual relationships as the basis in the transformation of their beliefs, adversely affecting their Islamic values in their virtual world. This subsequently resulted in the depersonalization of their personality, a bifurcation of their real and virtual personas. This shift of belief as manifested by the informants has potentially affected their perception and understanding of their Muslim religious and cultural identity, while undermining their Islamic faith and Aqidah. The study presents an e-personality model named “Tasarruf Persona” to characterize this emergent deviant phenomenon—a pervasive escapism, simulacra of wayward religious and sexual activity, contravening appropriate decorum and sacred tenets of the Islamic faith. The study concluded that the use of the Second Life virtual simulation has to be treated with care and proper guidelines must be implemented to prevent its negative impact on Islamic beliefs and religious practices.